DEVELOPING SUPPLEMENTARY ENGLISH-SPEAKING MATERIAL FOR THE SEVENTH GRADER OF ISLAMIC HIGH SCHOOL - Ahmad Shofi (Edulitics (Education, Literature, and Linguistics) Journal, 2019)
In this present globalization Era, teaching English with the goal as a tool for communication is necessary. In line with it, MTs Al Karimi 1, however, has commitment to create students to be able to use English as a tool for communication in everyday life. Due to the reason, this research has been conducted. This study aimed to develop English speaking materials and solve the problem during teaching and learning English for the seventh grader of Islamic High School. The study conducted in MTs Al Karimi 1 Gresik. The design of this study was Research and Development (R&D). The detail procedure of each step is elaborated in the procedure of the development. The researcher conduct this study with the following procedure: 1) identifying the problem; 2) reviewing the problem into the theory; 3) conducting need assessment and needs analysis; 4) gathering materials; 5) writing manuscript; 6) verifying to the expert; 7) revising; 8) validating to the experts. The result in this development was the supplementary English-speaking text book for the seventh grader of Islamic high school. The supplementary book contained the attractive cover, preface, table of contents, book mapping, colorful pictures and photos, good coherent and illustration. It has nine chapters with the topics which were chosen under the consideration of the students’ need. The strength of this product is on the basic common useful expressions, these basic common useful expressions are also translated to Indonesia equivalent since the students’ level of English proficiency is in intermediate level. By that way, the students are motivated and are easy to use the developed materials both inside and outside the classroom.